The impact of social network sites on academic performance among the undergraduate students of UiTM Sabah / Beverly Branda Edward ... [et al.] - Edward, Beverly Branda; Mayau, Ezra; Norman, Mohd Ariff Saifuddin; Nasir, Mohd Haliff (2014)
Since their introduction, social network sites (SNSs) such as MySpace, Facebook, Cyworld, and Bebo have attracted millions of users, many have using these sites into their daily practices. There are hundreds of SNSs, with various technological affordances, supporting a wide range of interests and practices. Most sites support the maintenance of previous social networks, but others help strangers connect based on shared interests, political views, or activities. Some sites provide to different audiences, while others to attract people based on common language or shared racial, sexual, religious, or nationality based identities. Social sites also vary in certain point which 'they include new information and communication tools, such as mobile connectivity, blogging, and photo/video-sharing. Social network is the use of internet-based social media programs to make connections with friends, family, classmates, customers and clients. Social networking can be done for social purposes such as for studies, business purposes or both. The programs show the associations between individuals and enable in gaining of new contacts. Examples of social networking have included Facebook, Twitter, Instagram, Linkedln, Classmates.com and Yelp. An attractive ways of communicating with other people that attracts all people regardless of their ages, occupation and social levels is through the Internet (Akbiyik, 2013). Connecting through the internet is now becoming a phenomenon, many college students have come to rely towards the usage of social networking that makes people feel as though they belong to a community and as a collaborative tool to create learning environment that improves learning performances, from taking note and even provide a venue for people to interact with other individuals. Despite the ability of face to face interactions, they use social networking so that they can virtually and maintain their communications independent from time and place even if they cannot physically meet (Akyuz et al., 2012). However, whether with the emergence of social networking that gives opportunities to enhance studies will give a positive or negative impacts is still a question that needs to be answered on its impacts on studies (Asemah & Communication, 2013).